One-step synthesis of highly-branched gold nanostructures and its application in fabrication of SERS-active substrates - Xiaowei Cao; Shuai Chen; Wei Li; Jianfeng Li; Liyan Bi; Hongcan Shi (AIP Advances, 2018)
In this paper, we reported a simple one-step synthesis of highly-branched gold nanostructures (HGNs) in high yields. The reduction of HAuCl4 was accomplished by dopamine hydrochloride in the reaction system. By varying the amount of dopamine hydrochloride, HAuCl4 and the reaction temperature, we managed to tune the size of the HGNs from 200 to 600 nm. Systematic analysis revealed that the optical properties and surface-enhanced Raman scattering (SERS) activities of the HGNs were highly dependent on their morphology and size. In terms of their SERS activities, it was found that the HGNs synthesized at 60 °C with 2.0 mL dopamine hydrochloride (53 mM), 0.4 mL HAuCl4 (50 mM) exhibited the largest SERS enhancement. When the HGNs were assembled onto the silicon wafers, outstanding SERS efficiency was obtained with a detection limit of 5×10-10 M of 4-mercaptobenzoic acid (4-MBA) and the analytical enhancement factor (AEF) was calculated to be 7×107. Besides, the 3-aminopropyltriethoxysilane (APTES)-functionalized substrates with the HGNs displayed remarkable signal reproducibility with relative standard deviation (RSD) of 3.57%. All these results demonstrated that the SERS-active substrates held great promise to be applied in trace-level molecule detection in the future.